Experimental and Numerical Investigations of Textile Hybrid Composites Subjected to Low Velocity Impact Loadings. (25th February 2014) - Chandekar, Gautam S.; Kelkar, Ajit D.
Abstract : In the present study experimental and numerical investigations were carried out to predict the low velocity impact response of four symmetric configurations: 10 ply E Glass, 10 ply AS4 Carbon, and two Hybrid combinations with 1 and 2 outer plies of E Glass and 8 and 6 inner plies of Carbon. All numerical investigations were performed using commercial finite element software, LS-DYNA. The test coupons were manufactured using the low cost Heated Vacuum Assisted Resin Transfer Molding (H-VARTM©) technique. Low velocity impact testing was carried out using an Instron Dynatup 8250 impact testing machine. Standard 6 × 6 Boeing fixture was used for all impact experiments. Impact experiments were performed over progressive damage, that is, from incipient damage till complete failure of the laminate in six successive impact energy levels for each configuration. The simulation results for the impact loading were compared with the experimental results. For both nonhybrid configurations, it was observed that the simulated results were in good agreement with the experimental results, whereas, for hybrid configurations, the simulated impact response was softer than the experimental response. Maximum impact load carrying capacity was also compared for all four configurations based on their areal density. It was observed that Hybrid262 configuration has superior impact load to areal density ratio.